Standardization of agro-techniques for aeroponic potato (Solanum tuberosum) minitubers under generation-0 - SADAWARTI, MURLIDHAR J; SAMADHIYA, R K; SINGH, R K; SINGH, S P; BUCKSETH, TANUJA; RAWAL, SANJAY; SINGH, VINAY; KATARE, SUBHAS; ROY, SATYAJIT; CHAKRABARTI, S K (The Indian Journal of Agricultural Sciences, 2020)
Since, very less information is available regarding the agro-techniques of hi-tech seed potato minitubers production, therefore an experiment was conducted to evaluate planting geometry and different doses of nitrogen for multiplication of aeroponic minitubers of potato (Solanum tuberosum L.) under net house conditions of north-central plains of India. 30 cm × 15 cm (97.44) plant geometry and 150 kg N/ha (95.81) and 180 kg N/ha (96.98) N dose recorded significantly higher emergence %. Linear increase in plant height was recorded with 120, 150 and 180 kg N/ha dose over 75 kg N/ ha (44.1 cm). Planting geometry 45 cm × 10 cm (34.71) and N dose 150 kg N (35.71) recorded significantly lowest per cent of <3 g minituber by number. Planting geometry 45 cm × 10 cm (1722 thousand/ha) followed by 30 cm × 10 cm (1587 thousand/ha) recorded significantly highest total tuber number over 30 cm × 15 cm (1209 thousand/ ha). Among N dose, 120 kg N (1560 thousand/ha) and 180 kg N/ha (1506 thousand/ha) dose recorded significantly higher total tuber number over 150 kg N/ha dose. Among interaction 45 cm × 10 cm with 120 kg N/ha dose recorded significantly highest total tuber number (1823 thousand/ha) over other combinations. For weight of tubers, 45 cm ×10 cm planting density with 150 kg N/ha reported highest tuber weight (27.62 t/ha). Hence, for the aeroponic seed multiplication of the variety Kufri Lauvkar, planting geometry of 45 cm × 10 cm with plant population of 222222 plants/ha and N, P2O5 and K2O ratio of 150:60:100 kg/ha should be adopted for getting higher tuber number and weight/ha.